Degradação em revestimentos externos argamassados de edificações públicas na cidade de Passo Fundo - Tessaro, Marta Rejane (2024)
The exposure of building façades to climatic agents makes them vulnerable to degradation, compromising the performance and durability of buildings over time. This study investigated the main pathological manifestations and degradation in external mortar coatings, using a determined degradation index evaluated on 84 façades of 25 school and administrative buildings in Passo Fundo, RS. Through visual inspections, pathological manifestations such as fissures, cracks, ruptures, broken blocks, detachment in plaques, pulverulence, blistering, discoloration, and paint peeling were identified. The methodology was based on determining the Damage Factor (DF), calculated by the area affected by each anomaly relative to the sample size, resulting in the General Damage Factor (GDF) as a function of the maintenance age of the façades. The results indicated that 44% of the samples had fissures, 22% paint peeling, 18% moisture stains, and 15% paint discoloration, with other manifestations ranging between 5.5% and 0.3%. The total DF exhibited expected behavior for the southern region of Brazil, with similar degradation between solar orientations (north and west at 26%, and south and east at 24%), except for fissures, which were not significantly affected by solar orientation. Regarding the severity of degradation, 52 samples were at Level 1, 22 at Level 2, and 6 at Level 3, with 2 samples showing degradation beyond the established levels, indicating an extent of 2.44%, corresponding to the end of the coating's service life. The age of maintenance was the variable with the greatest influence on degradation, with relatively low indices (GDF = 0.02) on façades up to 5 years old, and ranging from 0.007 to 0.154 between 19 and 31 years. A significant increase in GDF was observed between 6 and 12 years, depending on the façade's solar orientation.